Finance for managers - Luecke, Richard (Boston, Mass. : Harvard Business School Press, 2002)
Providing the fundamentals of financial literacy, this guide gives business managers the smart advice they need to increase their impact on financial planning, budgeting, and forcasting.
Financial statements -- Finding meaning in financial statements -- Important accounting concepts -- Taxes -- Financing operations and growth -- Money and capital markets -- Budgeting -- Practical tools for management decisions -- The time value of money -- Valuation concepts.
Includes bibliographical references (pages [200]-202) and index.
Description based on print version record.
Keywords: Corporations -- Finance; Business enterprises -- Finance; Analyse financière; Entreprises -- Finances; Finanzierung; Corporations -- Finance -- Management; Business enterprises -- Finance; Corporations -- Finance; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; elektronické knihy; electronic books